UV curing adhesive as well as preparation method and application thereof

By using polymer materials with a certain molecular weight, synergistically synergistically form macromolecular polymers with excellent bonding, solving the problems of high energy consumption, long curing time and poor strength of existing UV curing adhesives, and achieving the effects of low energy consumption, fast curing and high strength.

CN119570403APending Publication Date: 2025-03-07SICHUAN YUXI NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411784287.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing UV curing adhesives have problems such as high UV energy consumption, long curing time, poor peel strength and overlapping shear strength, which limits their application in opaque material bonding and electronic components production.

Method used

A polymer material with a certain molecular weight is used as the raw material for the UV curing reaction. Through synergistic effects, a macromolecular polymer with excellent adhesion is formed, which reduces curing energy consumption and time, and increases peel strength and overlapping shear strength.

Benefits of technology

It significantly reduces the energy consumption and curing time during adhesive curing, improves peel strength and overlapping shear strength, and is suitable for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a UV curing adhesive as well as a preparation method and application thereof, and belongs to the field of adhesives. The UV curing adhesive comprises the following raw materials in parts by weight: 20-70 parts of a reactive acrylate polymer, 8-40 parts of epoxy resin, 5-50 parts of core-shell rubber, 1-7 parts of a hydroxyl compound and 0.5-1 part of a cationic photoinitiator, according to the UV curing adhesive, a polymer material with a certain molecular weight is used as a raw material for a UV curing reaction, so that the adhesive has relatively good initial viscosity and is not easy to fall off after being adhered; under the action of a small amount of initiator, a macromolecular polymer with excellent cohesiveness can be formed through quick crosslinking, and the energy consumption and the curing time of the adhesive during curing are remarkably reduced; meanwhile, the peeling strength and the overlapping shear strength of the adhesive can be obviously improved; the UV curing adhesive has the advantages of low energy consumption, short curing time, high peel strength and overlapping shear strength, and is suitable for large-scale popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adhesives, mainly to the field of ultraviolet curing adhesives, and specifically to a UV curing adhesive and a preparation method and application thereof. Background Art

[0002] Many structural adhesives currently require heat to cure. In the process of manufacturing adhesive products, not only does it need to go through a heating step to cure the adhesive composition, but it also needs to be cooled for further processing and packaging as an adhesive product. From the perspective of energy saving and more convenient production, UV-curing adhesives that do not require heating, curing and cooling steps are obviously very market-advantageous and have great development prospects. UV-curing tape is a product containing an adhesive that can cure when exposed to ultraviolet rays. It does not require heat to cure, but heat can also be used to accelerate its curing rate.

[0003] Since UV-curing adhesive tapes or films need to have good mold cutting ability and initial strength when not cured, the UV-curing adhesive they contain needs to be composed of three parts: pressure-sensitive adhesive, curable components and photoinitiators. The UV curing principle can be divided into free radical curing system and cationic curing system. For UV free radical curing adhesives, the curing speed is too fast to form good bonding strength, and can only be used for bonding transparent surfaces; UV cationic curing tapes can be used for bonding opaque surfaces, and the curing speed can be adjusted, but the acid produced during the cationic curing process can easily cause corrosion to the metal surface; it can be seen that the principle of UV curing limits its scope of application.

[0004] In the production process of electronic components, production capacity and cost are also issues that need to be considered. The current cationic UV curing system has the problem of requiring energy (ultraviolet rays) and a slow curing time. For example, patent CN114174458A discloses a UV curable adhesive composition, the energy for UV curing of the adhesive composition is 1.5-3.0 J / cm 2 , the curing time is 48 hours. At the same time, existing UV curable adhesive products also have the problem of poor peel strength and overlapping shear strength. Therefore, when they are used in electronic devices, their impact resistance is low, and the bonding may be reduced or fail due to impact after bonding, thus affecting the stability and service life of electronic products.

[0005] Therefore, there is an urgent need for a UV curing adhesive that can be used for bonding opaque materials and has low UV energy consumption, fast curing time, and good peel strength and overlapping shear strength. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of high UV energy consumption, long curing time, poor peel strength and overlapping shear strength of existing UV curing adhesives, and propose a UV curing adhesive and a preparation method and application thereof.

[0007] To achieve the above-mentioned purpose, the present invention proposes a UV curing adhesive, comprising the following raw materials in parts by weight: 20-70 parts of reactive acrylate polymer, 8-40 parts of epoxy resin, 5-50 parts of core-shell rubber, 1-7 parts of hydroxyl compound, and 0.5-1 part of cationic photoinitiator.

[0008] The UV curing adhesive of the present invention uses a polymer material with a certain molecular weight as a raw material during UV curing reaction, so that not only a synergistic effect is formed between the raw materials, so that the adhesive has good initial adhesion and is not easy to fall off after being pasted; but also, during the UV curing reaction, under the action of less initiator, it can quickly cross-link to form a macromolecular polymer with excellent adhesion, thereby significantly reducing the energy consumption and curing time during the curing of the adhesive; at the same time, the curing reactant has a certain molecular weight, so that the compound after curing and cross-linking has fewer side chains, so that while having excellent adhesion, it also has better toughness, and the peeling strength and overlapping shear strength of the adhesive are significantly improved; the UV curing adhesive has the advantages of low energy consumption, short curing time, high peeling strength and overlapping shear strength, and is suitable for large-scale promotion and application.

[0009] The addition of reactive acrylate polymer increases the initial viscosity and has a significant effect on shortening the curing time, improving the peel strength and overlapping shear strength; the glass transition temperature of the reactive acrylate polymer is -34°C to 10°C.

[0010] Preferably, the acid value of the reactive acrylate polymer is not greater than 5.0 mg / g KOH; a low acid value means less corrosion to metals, and the polymer is more suitable for bonding metal materials.

[0011] Preferably, the reactive polyacrylate is polymerized from the following raw materials in parts by weight: 3-7 parts of hard monomer, 30-55 parts of soft monomer, 0.1-3.7 parts of functional monomer, 0.03-0.12 parts of regulator, 0.1-0.5 parts of initiator, and 35-40 parts of solvent.

[0012] Preferably, the functional monomer is acrylic acid and / or acrylic amide.

[0013] Preferably, the solvent is at least one of ethyl acetate (ETAC), toluene (TOL) and butanone (MEK).

[0014] Preferably, the hard monomer is at least one of methyl acrylate (MA), vinyl acetate (VAC), and isobornyl methacrylate.

[0015] Preferably, the soft monomer is at least one of n-butyl acrylate (n-BA), ethyl acrylate (EA), and isooctyl acrylate (2-EHA).

[0016] Preferably, the regulator is dodecyl mercaptan.

[0017] Preferably, the initiator is at least one of dibenzoyl peroxide (BPO) and azobisisobutyronitrile (AIBN).

[0018] Preferably, the method for preparing the reactive polyacrylate comprises the following steps: (1) mixing 40-60% by weight of a hard monomer, 40-60% by weight of a soft monomer, 40-60% by weight of a functional monomer, 40-60% by weight of a solvent and 100% by weight of a regulator in the raw materials to obtain a first mixed solution; (2) After heating the first mixed solution to 63-65° C. in a protective atmosphere, 15-25% by weight of an initiator is added to carry out a first prepolymerization reaction; (3) After the first prepolymerization reaction has been carried out for 50-70 minutes, all the remaining hard monomers, soft monomers and functional monomers and 10-20% by weight of initiator are added to carry out a second prepolymerization reaction; (4) After the second prepolymerization reaction lasts for 80-100 minutes, the temperature is raised to 73-75°C, all the remaining initiators are added, and the third polymerization reaction is carried out for 3-4 hours; (5) After the third polymerization reaction is completed, add all the remaining solvents and mix well to obtain reactive polyacrylate.

[0019] Preferably, the protective atmosphere in step (2) is a nitrogen atmosphere.

[0020] Preferably, the solid content of the reactive polyacrylate is 30-40%.

[0021] The addition of epoxy resin can significantly improve the initial adhesion and peel strength of the adhesive; the epoxy resin is a mixture of solid epoxy resin and liquid epoxy resin in a mass ratio of 1-3:2-3.

[0022] Among them, the addition of core-shell rubber can significantly improve the overlapping shear strength of the adhesive; the core of the core-shell rubber is at least one of polyisoprene, polybutadiene, and styrene-butadiene rubber copolymer; the shell of the core-shell rubber is at least one of acrylic polymers or copolymers; preferably, in the core-shell rubber, the mass percentage of the core accounts for 30-50%.

[0023] Among them, the hydroxy compound is used for cross-linking during curing, which can improve the peel strength and overlapping shear strength of the adhesive; preferably, the hydroxy compound is at least one of trimethylolpropane, pentaerythritol, polytetramethylene ether diol, polycarbonate diol, and polyether polyol.

[0024] Among them, preferably, the cationic photoinitiator is at least one of diazonium salts, diaryl iodonium salts, triaryl sulfonium salts, alkyl sulfonium salts, alkyl sulfonium salts, iron arene salts, sulfonyloxy ketones, and triaryl siloxane ethers.

[0025] To achieve the above object of the invention, the present invention further proposes a method for preparing a UV curing adhesive, comprising the following steps: uniformly mixing the above raw materials in parts by weight to obtain the UV curing adhesive.

[0026] To achieve the above-mentioned object of the invention, the present invention further proposes a use of a UV curing adhesive in the preparation of a UV curing adhesive tape and / or film.

[0027] Preferably, the UV curing adhesive tape comprises a PET substrate layer, a release layer and a glue layer disposed between the PET substrate layer and the release layer; the glue layer is coated with a UV curing adhesive.

[0028] Preferably, the UV curing adhesive film comprises two release layers with different release forces and a glue layer between the two release layers; the glue layer is formed by coating with a UV curing adhesive.

[0029] Compared with the prior art, the present invention has the following beneficial effects: 1. The UV curing adhesive of the present invention uses a polymer material with a certain molecular weight as a raw material for UV curing reaction, so that a synergistic effect is formed between the raw materials, so that the adhesive has good initial adhesion and is not easy to fall off after pasting.

[0030] 2. The UV curing adhesive of the present invention uses a polymer material with a certain molecular weight as a raw material for the UV curing reaction. During the UV curing reaction, under the action of less initiator, it can quickly cross-link to form a macromolecular polymer with excellent adhesion, thereby significantly reducing the energy consumption and curing time of the adhesive during curing.

[0031] 3. The UV curing adhesive of the present invention uses a polymer material with a certain molecular weight as a raw material for the UV curing reaction, so that the compound after curing and cross-linking has fewer branches, thereby having excellent adhesion and better toughness, and the peel strength and overlapping shear strength of the adhesive are significantly improved.

[0032] 4. The UV curing adhesive of the present invention has the advantages of low energy consumption, short curing time, high peel strength and overlapping shear strength, and is suitable for large-scale promotion and application.

[0033] 5. The UV curing adhesive of the present invention is used to prepare UV curing adhesive tapes and / or films, which can significantly improve the bonding performance of the tapes and / or films and expand the application field. The peeling force of the single-sided tape after curing can reach 4000 gf / 25mm (SUS steel plate), and the shear strength of the double-sided tape after curing can also reach 22MPa. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with test examples and specific implementation methods. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the content of the present invention belong to the scope of the present invention. Example 1

[0035] A UV curing adhesive comprises the following raw materials in parts by weight: 40 parts of reactive acrylate polymer, 20 parts of epoxy resin, 30 parts of core-shell rubber, 4 parts of hydroxyl compound (triether polyol), and 0.8 parts of cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of solid epoxy resin (NPES 901) and liquid epoxy resin (WSR 6101) in a mass ratio of 1:1; the core of the core-shell rubber is polybutadiene, the shell is acrylic polymer, and the mass percentage of the core is 40%; The reactive polyacrylate is polymerized by the following raw materials in parts by weight: 4 parts of hard monomer (methyl acrylate), 40 parts of soft monomer (ethyl acrylate), 2.5 parts of functional monomer (acrylic acid), 0.08 parts of regulator (dodecyl mercaptan), 0.3 parts of initiator (azobisisobutyronitrile), and 38 parts of solvent (ethyl acetate); The specific preparation method of reactive polyacrylate comprises: (1) mixing 50% by weight of a hard monomer, 50% by weight of a soft monomer, 50% by weight of a functional monomer, 50% by weight of a solvent and 100% by weight of a regulator in the raw materials to obtain a first mixed solution; (2) After heating the first mixed solution to 64° C. in a protective atmosphere, 20% by weight of an initiator was added to carry out a first prepolymerization reaction; (3) After the first prepolymerization reaction has been carried out for 60 minutes, all the remaining hard monomers, soft monomers and functional monomers and 15% by weight of initiator are added to carry out a second prepolymerization reaction; (4) After the second prepolymerization reaction for 90 minutes, the temperature was raised to 74°C, and all the remaining initiators were added, and the third polymerization reaction was carried out for 3.5 hours; (5) After the third polymerization reaction is completed, add all the remaining solvents and mix well to obtain a reactive acrylate polymer with a glass transition temperature of -12°C. Example 2

[0036] A UV curing adhesive comprises the following raw materials in parts by weight: 20 parts of reactive acrylate polymer, 8 parts of epoxy resin, 5 parts of core-shell rubber, 1 part of hydroxyl compound (polyether polyol), and 0.5 parts of cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of solid epoxy resin (NPES 901) and liquid epoxy resin (WSR 6101) in a mass ratio of 1:3; the core of the core-shell rubber is polybutadiene, the shell is acrylic polymer, and the mass percentage of the core is 40%; The formula and preparation method of the reactive polyacrylate are the same as those in Example 1. Example 3

[0037] A UV curing adhesive comprises a mixture of the following raw materials in parts by weight: 70 parts of reactive acrylate polymer, 40 parts of epoxy resin, 50 parts of core-shell rubber, 7 parts of hydroxyl compound (polyether polyol), and 1 part of cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of solid epoxy resin (NPES 901) and liquid epoxy resin (WSR 6101) in a mass ratio of 3:2; the core of the core-shell rubber is polybutadiene, the shell is acrylic polymer, and the mass percentage of the core is 40%.

[0038] The formula and preparation method of the reactive polyacrylate are the same as those in Example 1. Example 4

[0039] A UV curing adhesive comprises a mixture of the following raw materials in parts by weight: 40 parts of reactive acrylate polymer, 15 parts of epoxy resin, 25 parts of core-shell rubber, 5 parts of hydroxyl compound (trimethylolpropane), and 0.6 parts of cationic photoinitiator (diaryliodonium salt); the epoxy resin is a mixture of solid epoxy resin (NPES 901) and liquid epoxy resin (WSR 6101) in a mass ratio of 1:2; the core of the core-shell rubber is a styrene-butadiene rubber copolymer, and the shell is an acrylic copolymer, and the mass percentage of the core is 30%.

[0040] The reactive polyacrylate is polymerized by the following raw materials in parts by weight: 3 parts of hard monomer (vinyl acetate), 55 parts of soft monomer (isooctyl acrylate), 0.1 parts of functional monomer (acrylamide), 0.12 parts of regulator (dodecyl mercaptan), 0.1 parts of initiator (dibenzoyl peroxide), and 40 parts of solvent (toluene); The specific preparation method of reactive polyacrylate comprises: (1) mixing 40% by weight of a hard monomer, 40% by weight of a soft monomer, 40% by weight of a functional monomer, 40% by weight of a solvent and 100% by weight of a regulator in the raw materials to obtain a first mixed solution; (2) After heating the first mixed solution to 63° C. in a protective atmosphere, 25% by weight of an initiator was added to carry out a first prepolymerization reaction; (3) After the first prepolymerization reaction has been carried out for 70 minutes, all the remaining hard monomers, soft monomers and functional monomers and 10% by weight of initiator are added to carry out a second prepolymerization reaction; (4) After the second prepolymerization reaction lasts for 100 min, the temperature is raised to 73 °C, all the remaining initiators are added, and the third polymerization reaction is carried out for 3 h; (5) After the third polymerization reaction is completed, add all the remaining solvents and mix well to obtain a reactive acrylate polymer with a glass transition temperature of 10°C. Example 5

[0041] A UV curing adhesive comprises the following raw materials in parts by weight: 40 parts of reactive acrylate polymer, 20 parts of epoxy resin, 30 parts of core-shell rubber, 4 parts of hydroxyl compound (triether polyol), and 0.8 parts of cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of solid epoxy resin (NPES 901) and liquid epoxy resin (WSR 6101) in a mass ratio of 1:1; the core of the core-shell rubber is polybutadiene, the shell is acrylic polymer, and the mass percentage of the core is 40%; The reactive polyacrylate is polymerized from the following raw materials in parts by weight: 7 parts of hard monomer (isobornyl methacrylate), 30 parts of soft monomer (n-butyl acrylate), 3.7 parts of functional monomer (acrylamide), 0.03-0.12 parts of regulator (dodecyl mercaptan), 0.5 parts of initiator (azobisisobutyronitrile), and 35 parts of solvent (butanone); The specific preparation method of reactive polyacrylate comprises: (1) mixing 60% by weight of a hard monomer, 60% by weight of a soft monomer, 60% by weight of a functional monomer, 60% by weight of a solvent and 100% by weight of a regulator in the raw materials to obtain a first mixed solution; (2) After heating the first mixed solution to 65° C. in a protective atmosphere, 25% by weight of an initiator was added to carry out a first prepolymerization reaction; (3) After the first prepolymerization reaction has been carried out for 70 minutes, all the remaining hard monomers, soft monomers and functional monomers and 20% by weight of initiator are added to carry out a second prepolymerization reaction; (4) After the second prepolymerization reaction for 80 minutes, the temperature was raised to 75°C, all the remaining initiators were added, and the third polymerization reaction was carried out for 4 hours; (5) After the third polymerization reaction is completed, add all the remaining solvents and mix well to obtain a reactive acrylate polymer with a glass transition temperature of -34°C. Example 6

[0042] A UV curing adhesive comprises a mixture of the following raw materials in parts by weight: 60 parts of reactive acrylate polymer, 10 parts of epoxy resin, 20 parts of core-shell rubber, 7 parts of hydroxyl compound (polyether polyol), and 1 part of cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of solid epoxy resin (NPES 901) and liquid epoxy resin (WSR 6101) in a mass ratio of 3:2; the core of the core-shell rubber is a styrene-butadiene rubber copolymer, and the shell is an acrylic copolymer, and the mass percentage of the core is 55%.

[0043] The reactive polyacrylate is prepared by polymerization of the following raw materials in parts by weight: 7 parts of hard monomer (methyl acrylate), 55 parts of soft monomer (isooctyl acrylate), 0.17 parts of functional monomer (acrylic acid), 0.05 parts of regulator (dodecyl mercaptan), 0.4 parts of initiator (dibenzoyl peroxide), and 37 parts of solvent (toluene); The specific preparation method of reactive polyacrylate comprises: (1) mixing 50% by weight of a hard monomer, 60% by weight of a soft monomer, 40% by weight of a functional monomer, 60% by weight of a solvent and 100% by weight of a regulator in the raw materials to obtain a first mixed solution; (2) After heating the first mixed solution to 65° C. in a protective atmosphere, 25% by weight of an initiator was added to carry out a first prepolymerization reaction; (3) After the first prepolymerization reaction has been carried out for 50 minutes, all the remaining hard monomers, soft monomers and functional monomers and 10% by weight of initiator are added to carry out a second prepolymerization reaction; (4) After the second prepolymerization reaction lasts for 100 min, the temperature is raised to 73 °C, all the remaining initiators are added, and the third polymerization reaction is carried out for 3 h; (5) After the third polymerization reaction is completed, add all the remaining solvents and mix well to obtain a reactive acrylate polymer with a glass transition temperature of -25°C.

[0044] Comparative Example 1 A UV curing adhesive comprises the following raw materials in parts by weight: 40 parts of reactive acrylate polymer, 20 parts of epoxy resin, 30 parts of core-shell rubber, 4 parts of hydroxyl compound (triether polyol), and 0.8 parts of cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of solid epoxy resin (NPES 901) and liquid epoxy resin (WSR 6101) in a mass ratio of 1:1; the core of the core-shell rubber is polybutadiene, the shell is acrylic polymer, and the mass percentage of the core is 40%; The glass transition temperature of reactive polyacrylate is 15°C.

[0045] Comparative Example 2 A UV curing adhesive comprises the following raw materials in parts by weight: 40 parts of reactive acrylate polymer, 20 parts of epoxy resin, 30 parts of core-shell rubber, 4 parts of hydroxyl compound (triether polyol), and 0.8 parts of cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of solid epoxy resin (NPES 901) and liquid epoxy resin (WSR 6101) in a mass ratio of 1:1; the core of the core-shell rubber is polybutadiene, the shell is acrylic polymer, and the mass percentage of the core is 40%; The glass transition temperature of reactive polyacrylate is -36°C.

[0046] Comparative Example 3 A UV curing adhesive comprises a mixture of the following raw materials in parts by weight: 40 parts of a reactive acrylate polymer, 20 parts of an epoxy resin, 30 parts of a core-shell rubber, 4 parts of a hydroxyl compound (triether polyol), and 0.8 parts of a cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of a solid epoxy resin (NPES 901) and a liquid epoxy resin (WSR 6101) in a mass ratio of 3:1; the core of the core-shell rubber is polybutadiene, the shell is an acrylic polymer, and the mass percentage of the core is 40%; the reactive polyacrylate is the same as that in Example 1.

[0047] Comparative Example 4 A UV curing adhesive comprises a mixture of the following raw materials in parts by weight: 40 parts of a reactive acrylate polymer, 20 parts of an epoxy resin, 30 parts of a core-shell rubber, 4 parts of a hydroxyl compound (triether polyol), and 0.8 parts of a cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of a solid epoxy resin (NPES 901) and a liquid epoxy resin (WSR 6101) in a mass ratio of 1:4; the core of the core-shell rubber is polybutadiene, the shell is an acrylic polymer, and the mass percentage of the core is 40%; the reactive polyacrylate is the same as that in Example 1.

[0048] Comparative Example 5 A UV curing adhesive comprises the following raw materials in parts by weight: 40 parts of reactive acrylate polymer, 20 parts of epoxy resin, 30 parts of core-shell rubber, and 0.8 parts of cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of solid epoxy resin (NPES 901) and liquid epoxy resin (WSR 6101) in a mass ratio of 1:1; the core of the core-shell rubber is polybutadiene, the shell is an acrylic polymer, and the mass percentage of the core is 40%; the reactive polyacrylate is the same as that in Example 1.

[0049] Comparative Example 6 A UV curing adhesive comprises a mixture of the following raw materials in parts by weight: 40 parts of a reactive acrylate polymer, 20 parts of an epoxy resin, 4 parts of a hydroxyl compound (triether polyol), and 0.8 parts of a cationic photoinitiator (Uyracure-180); the epoxy resin is a mixture of a solid epoxy resin (NPES 901) and a liquid epoxy resin (WSR 6101) in a mass ratio of 1:1; the reactive polyacrylate is the same as that in Example 1.

[0050] Experimental example: The UV-curable adhesive prepared in the above Examples 1-6 and Comparative Examples 1-6 was coated on a substrate (original PET film / heavy release film) to have a thickness of 50 μm to form a UV-curable adhesive tape / film.

[0051] The properties (peel strength and shear force before and after curing) of the UV-curing adhesives and the corresponding UV-curing adhesive tapes in the above Examples 1-6 and Comparative Examples 1-6 were tested, and the energy required for curing and the curing time of the UV-curing adhesives in each Example and Comparative Example were detected. The test standards and methods are as follows: Test the peel force after curing: The force required to peel the tape at 180° is measured in the test. Refer to the peel force test method ASTM D3330; first use UV irradiation (LED 365nm, 1 J / cm) to trigger the curing process; then cut the 50 μm thick tape (backing: 50 μmPET) into 25*200mm, attach it to a stainless steel plate and roll it twice with 2kg force. The test sample strips are then placed in a room with a controlled environment (23℃ / 50% relative humidity) and tested after curing for about 12 hours (or 4 hours at 70℃); the initial peel force is tested at the same time (uncured, placed for 20min). The recorded values ​​are the average of three samples; Overlap shear adhesion test after curing: Overlap shear adhesion was evaluated using a 25*100 mm steel plate. The curing process was first triggered by UV (LED 365nm, 1 J / cm). After irradiation, one side of the adhesive film was attached to about 12.5 mm above the upper end of the steel plate. The film was rolled up and pressed twice with a force of 2 kg, and then the redundant adhesive film on the edge was cut. The PET release profile on the surface was immediately peeled off, and the steel plates on the other side were joined face to face along their length to provide an overlapping bonding area of ​​about 25*12.5 mm. The test sample strips were then placed in a room with a controlled environment (23°C / 50% relative humidity) and tested after curing for about 12 hours (or 4 hours at 70°C); the shear force without UV curing was tested in parallel. The recorded values ​​are the average of three samples.

[0052] Curing energy: The minimum energy required for the peeling force to reach 3000gf / mm when cured for the same time using UV lamp (LED365nm).

[0053] Curing time: The shortest time required for the peeling force to reach 3000gf / mm under irradiation with UV lamp (LED365nm, 1J / cm).

[0054] The test results are as follows:

[0055] From the experimental results in the analysis table, it can be seen that the present invention uses a polymer material with a certain molecular weight as a raw material for UV curing reaction, so that the UV curing adhesive has the advantages of low energy consumption, short curing time, high peel strength and overlapping shear strength, and is suitable for large-scale promotion and application.

Claims

1. A UV curing adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 20-70 parts of reactive acrylate polymer, 8-40 parts of epoxy resin, 5-50 parts of core-shell rubber, 1-7 parts of hydroxyl compound and 0.5-1 parts of cationic photoinitiator; the glass transition temperature of the reactive acrylate polymer is -34°C to 10°C; the epoxy resin is a mixture of solid epoxy resin and liquid epoxy resin in a mass ratio of 1-3:2-3; the core of the core-shell rubber is at least one of polyisoprene, polybutadiene and styrene-butadiene rubber copolymer, and the shell of the core-shell rubber is at least one of acrylic polymers or copolymers.

2. The UV curing adhesive according to claim 1, characterized in that: The reactive polyacrylate is polymerized from the following raw materials in parts by weight: 3-7 parts of hard monomer, 30-55 parts of soft monomer, 0.1-3.7 parts of functional monomer, 0.03-0.12 parts of regulator, 0.1-0.5 parts of initiator, and 35-40 parts of solvent; The functional monomer is acrylic acid and / or acrylamide; the solvent is at least one of ethyl acetate, toluene and butanone; the hard monomer is at least one of methyl acrylate, vinyl acetate and isobornyl methacrylate; the soft monomer is at least one of n-butyl acrylate, ethyl acrylate and isooctyl acrylate; the regulator is dodecyl mercaptan; and the initiator is at least one of dibenzoyl peroxide and azobisisobutyronitrile.

3. The UV curing adhesive according to claim 2, characterized in that: The preparation method of the reactive polyacrylate comprises the following steps: (1) mixing 40-60% by weight of a hard monomer, 40-60% by weight of a soft monomer, 40-60% by weight of a functional monomer, 40-60% by weight of a solvent and 100% by weight of a regulator in the raw materials to obtain a first mixed solution; (2) After heating the first mixed solution to 63-65° C. in a protective atmosphere, 15-25% by weight of an initiator is added to carry out a first prepolymerization reaction; (3) After the first prepolymerization reaction has been carried out for 50-70 minutes, all the remaining hard monomers, soft monomers and functional monomers and 10-20% by weight of initiator are added to carry out a second prepolymerization reaction; (4) After the second prepolymerization reaction lasts for 80-100 minutes, the temperature is raised to 73-75°C, all the remaining initiators are added, and the third polymerization reaction is carried out for 3-4 hours; (5) After the third polymerization reaction is completed, add all the remaining solvents and mix well to obtain reactive polyacrylate.

4. The UV curing adhesive according to claim 3, characterized in that: The solid content of the reactive polyacrylate is 30-40%.

5. The UV curing adhesive according to claim 1, characterized in that: In the core-shell rubber, the mass percentage of the core is 30-50%.

6. The UV curing adhesive according to claim 1, characterized in that: The hydroxy compound is at least one of trimethylolpropane, pentaerythritol, polytetramethylene ether diol, polycarbonate diol and polyether polyol.

7. The UV curing adhesive according to claim 1, characterized in that: The cationic photoinitiator is at least one of diazonium salts, diaryl iodonium salts, triaryl sulfonium salts, alkyl sulfonium salts, alkyl sulfonium salts, iron arene salts, sulfonyloxy ketones, and triaryl siloxane ethers.

8. Use of the UV curing adhesive according to any one of claims 1 to 7 in the preparation of UV curing adhesive tapes and / or films.

9. The use of the UV curing adhesive according to claim 8, characterized in that: The UV curing adhesive tape comprises a PET substrate layer, a release layer and a glue layer arranged between the PET substrate layer and the release layer; the glue layer is formed by coating with a UV curing adhesive.

10. The use of the UV curing adhesive according to claim 8, characterized in that: The UV curing adhesive film comprises two release layers with different release forces and a glue layer between the two release layers; the glue layer is formed by coating with a UV curing adhesive.

Citation Information

Cited By

  • Preparation method of ultraviolet light and heat dual-curing pressure-sensitive adhesive

    CN120310474A